Analisis Biaya Dan Waktu Pada Proyek Pembangunan Gedung Dengan Metode Earned Value Pada Proyek Pembangunan Gedung F Universitas Pekalongan - Annasir, M. Abdul Malik; Tisnawati, Tisnawati; Putri, Sabrina Amelia (Universitas Teuku Umar, 2024)
Projects are structured activities conducted within a specific timeframe to achieve defined objectives by utilizing allocated resources.. Projects are also limited by time by the contract agreement. If this is not implemented and handled properly, it will have a negative impact which will ultimately lead to failure to achieve the desired goals and objectives. During the process of achieving these goals, some limitations must be met. The concept of performance value is a method to measure project progress by using three key metrics: BCWS, BCWP, and ACWP. This method calculates the budgeted costs based on the work that has been completed or executed (budgeted costs of the work performed). The research process starts with actualization, data collection, conducting direct project interviews, and synthesizing the outcomes of the collected data. This study aims to determine the estimated cost and time involved, as well as to calculate the cost and time needed to complete the project work. Based on the methodological analysis of the 55th week of the Pekalongan University Building F construction project, the schedule deviation value (SV) is Rp. 0. These results indicate that the work performance reaches 100, compared to the plan. While the Cost Variance (CV) is Rp. 19,693,765,800, these results indicate that the work carried out with the costs used is the same as the planned contract even though it is carried out by an addendum. Project Completion Time (PDT) = 55 weeks estimated, which means it tends to be an additional 8 weeks, whereas completing the project on schedule takes only 47 weeks. Keywords: Income Value Method, ACWP, BCWP, BCWS, SV, CV, ECD